Translation Analysis of the Article in National Geographic Magazine Entitled “The End of Trash” by Robert Kunzig, 2020 Edition - Awali, Dafa Maora; Larassati, Anisa (Universitas Dian Nuswantoro, 2024)
This study aimed to identify the translation techniques and quality of the article